2019
DOI: 10.1039/c8na00132d
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro efficient textile wastewater remediation by Aspergillus niger biosorbent

Abstract: We report a facile and high-efficiency technology using eco-friendly Aspergillus niger as a biosorbent to treat textile wastewater. Excellent adsorption ability with nearly 98% decoloration was achieved. The bioadsorption technology could be used to fight environmental damage caused by organic or inorganic pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 39 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…The morphology of M. purpureus in submerged media is a compact, smooth, and spherical pellet consisting of intertwined hyphae [ 52 , 53 , 54 ]. Consistent with studies on other filamentous fungi, we found that dry weight measurement is the most reproducible method of quantifying M. purpureus growth [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 89%
“…The morphology of M. purpureus in submerged media is a compact, smooth, and spherical pellet consisting of intertwined hyphae [ 52 , 53 , 54 ]. Consistent with studies on other filamentous fungi, we found that dry weight measurement is the most reproducible method of quantifying M. purpureus growth [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Resultssupporting
confidence: 89%
“…where, C is −17.7 ng/cm 2 and is a constant value for 5 MHz crystals, ∆f is the change of frequency, and n is the overtone number. However, most of the polymeric systems do not generate a rigid layer to result in underestimation of the adsorbed mass using Equation 3. Some other models have been developed to address the change in mass, such as Voigt's and Maxwell's that considered the density, and dynamic and static viscosity of the adsorbed materials, as well as the crystals [44].…”
Section: Quartz Crystal Microbalance With Dissipation Monitoring (Qcm-d)mentioning
confidence: 99%
“…The demand for green materials has led to an increase in the development of materials derived from natural sources [1,2], especially when adsorption and removal of pollutants is the target application. This natural adsorbent can vary from composites derived from whole organisms such as Aspergillus [3], to more selective composites based on biopolymers, such as chitosan [4], or the more abundant cellulose. This latter one is the main component of cell wall structures of plants, algae, and a few other organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations